IFDC opens African office-to improve fertilizer usage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
IFDC (the International Fertilizer Development Centre) has recently set up its African regional centre in Togo near the Togo Phosphates Bureau. Together with other national, regional, and international bodies. This organization directs research on...